Water-soluble polymer anchored peroxotitanates as environmentally clean and recyclable catalysts for mild and selective oxidation of sulfides with H2O2 in water. Issue 44 (1st November 2019) - Ahmed, Kabirun; Saikia, Gangutri; Paul, Sivangi; Baruah, Satyajit Dey; Talukdar, Hiya; Sharma, Mitu; Islam, Nashreen S.
Abstract: Anchoring of peroxotitanium (pTi) species to linear water-soluble acrylic acid based polymers, poly(sodium acrylate) (PA) and poly(sodium methacrylate) (PMA) led to the successful synthesis of a pair of new, water-tolerant and recyclable catalysts of the type [Ti2 (O2 )2 O2 (OH)2 ] 4- —L (L = PA or PMA), highly effective in chemoselective sulfoxidation of organic sulfides with 30% H2 O2 in aqueous medium at ambient temperature. The catalytic protocol is high yielding (TOF up to 11, 280 h −1 ), operationally simple as well as environmentally clean and safe, being free from halide, or any other toxic auxiliaries. The catalysts are sufficiently stable to afford easy recyclability for at least 10 consecutive reaction cycles of sulfoxidation with consistent activity selectivity profile. Oxidation of dibenzothiophene (DBT) to respective high purity sulfoxide or sulfone could also be accomplished using the same catalysts by variation of reaction conditions. Graphical abstract: Image 1 Highlights: Peroxotitanium(IV) complexes supported on non-cross linked water soluble polymers served as eco-compatible catalysts for chemoselective sulfoxidation in aqueous medium. The catalytic procedure is high yielding, operationally simple and free from halogenated solvents. The catalysts are stable and recyclable for at least ten cycles of consecutive sulfoxidation. The catalysts also support oxidation of dibenzothiophene(DBT) with H2 O2 to the corresponding sulfoxide or sulfone.